The Titanic series: Reflections on Cambridge University Press’s edition of the literary works of Joseph Conrad - Watts, Cedric (Adam Mickiewicz University, 2019)
Cambridge University Press’s vast project to produce authoritative new editions of the literary works of Joseph Conrad is now well advanced; but the project is flawed. I maintain that this is the Titanic of editions: big, costly, important, and disastrous. I specify “the literary works”, because I am not concerned with the admirable volumes of Conrad’s letters. The industrious Cambridge editors have done excellent work in correcting longstanding errors and in bringing to light much textual material which was previously lost. The edition is therefore indispensable. The editors have, however, deleted much house styling and correction: “successive layers of non-authorial intervention affecting wording and ‘accidentals’ – punctuation, spelling and word-division”. The result of the Cambridge editorial procedures is a Conradian prose which is often impoverished and is sometimes even ungrammatical and uncouth. In removing much punctuation, the editors have often removed logical clarity and rhetorical effectiveness. In this essay, therefore, I use a sequence of comparisons to demonstrate the presence of a pattern of flaws. The sequences are taken from Notes on Life and Letters, ’Twixt Land and Sea / Tales, Last Essays, Lord Jim, and The Nigger of the “Narcissus”. I compare extracts from the Cambridge texts with extracts taken from other editions.
Keywords: Cambridge University Press; Joseph Conrad; editions; editorial criteria; house styling; logical clarity; rhetorical effectiveness